MARKETING MIX TO ENHANCE MARKETING PERFORMANCE IN SMEs OF KERUPUK GENDAR MIRASA AT BANYUMAS REGENCY - Uripi, Cahyaningtyas Ria; Arinastuti, Arinastuti; Setiawan, Heri; Rahayuningtyas, Denit Adristi (Journal of Community Service, 2022)
Micro, Small and Medium Enterprises (MSMEs) were the drivers of the economy in Indonesia. MSMEs have some limitations, including in knowledge and capabilities in the field of marketing. The marketing mix is a marketing strategy consisting of product, price, place and promotion elements. Community Service Activities for Kerupuk Gendar Mirasa UMKM in Banyumas Regency are carried out through the transfer of knowledge and skills about the Marketing Mix. The activities carried out are product development, selection of raw materials, accuracy of composition of raw materials, use of tools so that they can make crispy and tasty crackers. The activities give the training abaout product packaging, product branding, determining selling prices and promotions. The result of the activity is the good transfer of knowledge and skills regarding the marketing mix, so as to increase sales and profits as well as marketing performance.